The defensive Spiroplasma - Ballinger, Matthew J; Perlman, Steve J (Current opinion in insect science, 2019)
•Multiple strains of the heritable bacterium, Spiroplasma, protect insects against infection by natural enemies.•Defensive capabilities are broad, impacting parasitic nematodes, insects, and fungi.•A mechanism is implicated — toxic ribosome-inactivating proteins are common across Spiroplasma.•Model hosts and culturability position Spiroplasma as an exceptional model for the study of defensive symbiosis. Defensive microbes are of great interest for their roles in arthropod health, disease transmission, and biocontrol efforts. Obligate bacterial passengers of arthropods, such as Spiroplasma, confer protection against the natural enemies of their hosts to improve their own fitness. Although known for less than a decade, Spiroplasma’s defensive reach extends to diverse parasites, both microbial and multicellular. We provide an overview of known defensive phenotypes against nematodes, parasitoid wasps, and fungi, and highlight recent studies supporting the role of Spiroplasma-encoded ribosome-inactivating proteins in protection. With cellular features well-suited for life in the hemolymph, broad distribution among invertebrate hosts, and the capacity to repeatedly evolve vertical transmission, Spiroplasma may be uniquely equipped to form intimate, defensive associations to combat extracellular parasites. Along with insights into defensive mechanisms, recent significant advances have been made in male-killing — a phenotype with interesting evolutionary ties to defense. Finally, we look forward to an exciting decade using the genetic tools of Drosophila, and the rapidly-advancing tractability of Spiroplasma itself, to better understand mechanisms and evolution in defensive symbiosis.